2009
DOI: 10.1029/2009gl039026
|View full text |Cite
|
Sign up to set email alerts
|

Atypical influence of the 2007 La Niña on rainfall and temperature in southeastern Australia

Abstract: Interannual climate variations associated with El Niño – Southern Oscillation (ENSO) dominate rainfall and temperature variability in southeastern Australia's Murray‐Darling Basin (MDB), an important region for agricultural productivity. Following a decade‐long dry period, a La Niña during 2007 failed to provide above average rainfall and cool temperatures in the southern half of the MDB, typical of most La Niña events for the region. Instead, annual (winter half‐year) rainfall was 17% (35%) below average and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
4
14
0
Order By: Relevance
“…The rankings from Table 2 are also in agreement with and Verdon-Kidd and Kiem (2009b) who suggested that a consistently positive SAM since the 1990s, associated with a poleward retraction of the mid-latitude storm track (Frederiksen et al, 2011), may be responsible for the recent trends in southeast Australian rainfall. However, there are some conflicts between these results and other studies that show there are no significant associations between southeast Australian autumn rainfall and the SAM ).…”
Section: Small-scale Evolutionsupporting
confidence: 77%
See 2 more Smart Citations
“…The rankings from Table 2 are also in agreement with and Verdon-Kidd and Kiem (2009b) who suggested that a consistently positive SAM since the 1990s, associated with a poleward retraction of the mid-latitude storm track (Frederiksen et al, 2011), may be responsible for the recent trends in southeast Australian rainfall. However, there are some conflicts between these results and other studies that show there are no significant associations between southeast Australian autumn rainfall and the SAM ).…”
Section: Small-scale Evolutionsupporting
confidence: 77%
“…3 and 4, which are very important (see later discussion). Further, longer term trends in some inter-annual processes have recently been identified including an increase in the intensity of the STR (Drosdowsky, 2005;Larsen and Nicholls, 2009;Williams and Stone, 2009) and a poleward retraction of the mid-latitude storm belt (Frederiksen et al, 2011) which is consistent with trends towards a more positive SAM (Marshall, 2003). As such, these trends have also been included and assessed in Table 2 as potential causal mechanisms of the Big Dry.…”
Section: Small-scale Evolutionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the maximum temperature anomaly is anomalously high (figure not shown). It therefore seems that the low probability of only 2% for the combined anomalies during a La Niñ a year (Gallant and Karoly 2009) is largely due to the maximum temperature, not the precipitation. However, it should be noted that the regions investigated do not completely coincide.…”
mentioning
confidence: 99%
“…The only exception is September, when 70% of La Niñ as record above-average precipitation. Gallant and Karoly (2009) described unusual conditions over SEA during the La Niñ a of 2007, with winter rainfall 35% below average and maximum temperatures 1.268C above average. Based on past variability, they concluded that only 2% of La Niñ a events were likely to have this combined precipitation and temperature anomaly over the southern regions of the MDB and suggested modulating influences by the pIOD during 2007.…”
mentioning
confidence: 99%